A framework of hiring strategy for manpower hiring in a hyper-local food delivery organization. Issue 1 (17th August 2020) - Das, Debadyuti; Yadav, Chirag
Abstract : Purpose: The present work attempts to determine an appropriate number of different categories of Delivery Persons for a Hyper-local Food Delivery Organization for different intervals within a day and across days within a week which would provide a satisfactory level of service to the target customers and at the same time would become cost-efficient. Design/methodology/approach: Currently the firm estimates the required number of Delivery Persons for "lunch peak" and "dinner peak" of the next week's weekdays and weekend based on the maximum number of orders occurring during the same period of both weekdays and weekend in the current week. The proposed approach involves determining the projected demand in every four-hourly interval of both week-days and weekend in the next week. Subsequently, the study has developed a simple integer programming model for determining the optimum number of Delivery Persons based on the projected demand data. Findings: The existing approach followed by the firm indicates that the Delivery Persons remain unutilized during periods of low demand. The proposed model demonstrated savings to the tune of 21.4% in manpower cost without any erosion in the service level. Originality/value: The study has made three tangible contributions. First, the development of a simple methodology for estimating the demand of next period allows the Managers to utilize dynamic demand data. Second, the development of a simple integer programming model helps managers determine an appropriate number of Delivery Persons in different intervals in both weekdays and weekend. Third, the development of a framework of hiring strategy aids managers in adopting a particular hiring strategy under a particular context keeping in mind the magnitude of demand for food, demand for delivery service and the cost of providing the service.